A Review on CBIR with its Advantages and Disadvantages For Low-level Features - Pandey, Dharmendra; Kushwah, Shivpratap (International Journal of Computer Sciences and Engineering, 2025)
The requirement for development of CBIR is enhanced as a result of giant progress in volume of snap shots as good as the preferred software in a more than one fields.spatial layout, shape, colour, and texture are the special qualities to represent by the table of contents images. These peculiar points by snap shots are extracted and applied for a similarity assess among graphics.. The paper offers a overview on various approaches of content based photo retrieval (CBIR). CBIR is a process throught which different images are retrieved by a giant database collection. These databases are prepared using various visual features Like. spatial layout, shape, colour, and texture that are extracted making use of different techniques. As image database volume is increasing rapidly, researchers are looking to a better mechanism to retrieve images and to obtain more accurate results.